Analysis of opportunities to implement Steam driven fans in new formaldehyde plants - Shah, Syed Amir Ali (My University, 2012)
The purpose of this Master thesis (project) is to perform a conceptual design and an economic viability study of steam turbine system for production of power which can be used to partially or totally cover the power requirements of the recirculation blowers in a chemical process. In this project a process for production of 52500 ton/year of Formaldehyde 37 wt% with a consumption of 22300 ton/year of Methanol has been studied. Based on a reactor using metal oxide catalyst, formaldehyde is produced by means of methanol catalytic oxidation. The formalin plant operates slightly above the atmospheric pressure. The speed of the recirculation blowers increases in order to overcome the pressure drop that occurs in reactor when the catalyst is getting old. Due to degradation of the catalyst the pressure drop increases therefore at some point the pressure drop reach a level where the catalyst must be replaced with new catalyst. The oxidation is highly exothermic. In order to promote the high conversion of methanol the reaction is kept at given temperatures by means of oil cooling HTF. Oil cooling is achieved by generating steam from condensate. In the standard process, steam is produced at medium pressure. Process heat integration analysis is carried out to find the maximum thermodynamic potential of power generation. The maximum steam superheating temperature and steam mass flow rate are estimated by means of simple Pinch Analysis calculations. By comparing the power production potential and the power consumption over an average year, different possible design solutions for turbo machinery arrangement (Single Shaft or Double shaft system) are considered and two main design options from vendors are discussed. The different designs are compared considering two main profitability criteria: payback time and net present value. In particular, the total investment cost for single shaft design is around 334’000 €. The revenues in terms of electricity savings is around 146’000 €/year. The payback time for this system is 3 years. The total investment cost for double shaft design is around 200’000 € and the revenues in terms of electricity savings is around 94’000 €/year. The payback time is also 3 years for this design. While the pay-back time does not help to identify the best system option, a discounted cash flow analysis shows that the net present value at the end of 10 year is higher for the single shaft system compared to the double shaft system case.
Keywords: Kemiska processer; Chemical Process Engineering